Internal mechanisms for establishment of the equilibrium state of water-alcohol mixtures in vodka technology - Kuzmin, Oleg; Zubkova, Valentyna; Shendrik, Tatiana; Korenets, Yuriі; Kuzmin, Anton; Bilenky, Pavel (My University, 2018)
The aim of the publication is to study the mechanism of the establishment of relaxation of water-alcohol mixtures in the main stages of creating vodka in the application of electrochemical activation at the stage of Na-cationization process water softening.Метою публікації є дослідження механізму встановлення релаксації водно-спиртових сумішей на основних етапах створення горілки при застосуванні електрохімічної активації на стадії Na-катіонного зм’якшення технологічної води.
Keywords: water-alcohol mixture; Na-cationization; electrochemical activation; hydroxyl protons; водно-спиртова суміш; Na-катіонування; електрохімічна активація; гідроксильні протони; кафедра технології ресторанної і аюрведичної продукції